2013
DOI: 10.30638/eemj.2013.034
|View full text |Cite
|
Sign up to set email alerts
|

Romanian Surface Water Quality: Tarnava Mare River Between Medias and Copsa Mica Case Study

Abstract: A set of 500 water samples collected from various sites of Tarnava Mare River, between Medias and Copsa Mica were analyzed, during three years (2010)(2011)(2012). The physicochemical parameters like: temperature, pH, electrical conductivity (EC), total dissolved solids (TDS), salinity, calcium (Ca . It was found that the water samples collected from various sites were contaminated with chloride, nitrate and nitrite. Since health, plant and animal life can be affected, the system needs to be monitored and impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The spatial variation of NO3-N showed the minimum and maximum values of 0.6±0.1 mg/L at Z3 and 1.9±0.5 mg/L at Z6 (p < 0.01), respectively (Figure 3d). According to Ayers and Westcot [9], the degree of restriction for NO3-N in Burullus Lake on reuse was "None". However, the increase in NO3-N concentration over 0.3 mg/L suggests the occurrence of eutrophication.…”
Section: Biological Oxygen Demandmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial variation of NO3-N showed the minimum and maximum values of 0.6±0.1 mg/L at Z3 and 1.9±0.5 mg/L at Z6 (p < 0.01), respectively (Figure 3d). According to Ayers and Westcot [9], the degree of restriction for NO3-N in Burullus Lake on reuse was "None". However, the increase in NO3-N concentration over 0.3 mg/L suggests the occurrence of eutrophication.…”
Section: Biological Oxygen Demandmentioning
confidence: 99%
“…The increased concentration of PO4-P at Z2 (2.2±0.4 mg/L), Z4 (3.3±0.8 mg/L), and Z6 (4.8±0.2 mg/L) could result from the discharges of drains [7][8][9] (Figure 3d). Similarly, El-Zeiny & El-Kafrawy [5] indicated that the increase in the percentage of agricultural and urban lands contributed to an increment of nutrient concentrations in lake ecosystems.…”
Section: Biological Oxygen Demandmentioning
confidence: 99%